EFFECT OF STORAGE CONDITIONS (GROWTH CHAMBER) AND IBA TREATMENTS ON ROOTING OF CUTTINGS OF APPLE CLONAL ROOTSTOCK MERTON 793 IN NET HOUSE CONDITIONS - PRAMOD VERM; P. S. CHAUHAN (The Bioscan, 2015)
The study on controlled preconditioning storage conditions (growth chamber) and IBA treatments on rooting of cuttings of apple clonal rootstock Merton 793 was carried out in net house conditions of fruit nursery block of Department of Fruit Science, Dr. Y. S. Parmar University of Horticulture and Forestry Nauni, Solan H.P. during 2012-2013. The cuttings were stored at 22 ≤ C with 80 % relative humidity in growth chamber for 7 days, 14 days, 21 days and 28 days as preconditioning treatment and different IBA concentrations of 1500 ppm, 2000 ppm, 2500 ppm and 3000 ppm were applied. The experiment was laid out in randomized block design (factorial) The cuttings stored for 7 days along with IBA 2500 ppm treatment recorded highest rooting percentage, number of primary roots, length and diameter of primary roots, fresh and dry weight of roots recording 46.67 %, 4.60, 28.60 cm, 2.63 mm, 2.89g and 1.83 g, respectively. Hence it is concluded that cuttings when stored in growth chamber for a period of 7 days treated along with IBA 2500 ppm were found to best for better rooting in apple clonal rootstock Merton 793.